2016
DOI: 10.2337/dc15-2579
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hemoglobin A1c Between Hispanics/Latinos and Non-Hispanic Whites: An Analysis of the Hispanic Community Health Study/Study of Latinos and the 2007–2012 National Health and Nutrition Examination Survey

Abstract: OBJECTIVETo determine whether, after adjustment for glycemia and other selected covariates, hemoglobin A1c (HbA1c) differed among adults from six Hispanic/Latino heritage groups (Central American, Cuban, Dominican, Mexican, Puerto Rican, and South American) and between Hispanic/Latino and non-Hispanic white adults without self-reported diabetes.RESEARCH DESIGN AND METHODSWe performed a cross-sectional analysis of data from 13,083 individuals without self-reported diabetes from six Hispanic/Latino heritage grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…We recognize that these findings have been previously reported ( 25 , 26 ), but to our knowledge, this is the first time this issue has been explored in a low-income, elderly, urban, and predominantly obese Mexican population. Perhaps the previously-mentioned characteristics might explain the magnitude of its frequency.…”
Section: Discussionsupporting
confidence: 73%
“…We recognize that these findings have been previously reported ( 25 , 26 ), but to our knowledge, this is the first time this issue has been explored in a low-income, elderly, urban, and predominantly obese Mexican population. Perhaps the previously-mentioned characteristics might explain the magnitude of its frequency.…”
Section: Discussionsupporting
confidence: 73%
“…Its normal range in adult populations is up to 5.7% (39 mmol/mol) 2 4 . HbA1c levels in adults show age-, sex-, and ethnicity-related differences, implying the need to establish reference values according to relevant factors 5 7 . Only a few population-based studies on HbA1c reference values have been performed to date 8 , 9 ; these have demonstrated differences in the distribution of HbA1c values based on age, sex, and ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the rapidly increasing prevalence of obesity and type 2 DM in children and adolescents, and the increasing use of HbA1c as a marker of glucose metabolism, it is important to establish normative reference values for the Korean population. Normative studies of children and adolescents, mostly conducted in the USA, showed differences in the distribution of HbA1c values based on age; values tended to be higher during adolescence 5 , 8 , 9 . The aims of the present study were to describe the normative distribution of HbA1c values and to investigate the factors associated with HbA1c values in Korean youths and young adults, using nationally representative data.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among low-income, elderly Mexicans showed disagreement between OGTT and HbA1c measurements, suggesting possible misclassification when using HbA1c alone [53]. Other studies have confirmed significantly higher levels of HbA1c for Hispanics compared to non-Hispanic whites in the U.S. [54, 55]. …”
Section: Discussionmentioning
confidence: 99%